Pelatihan Pembuatan Produk Olahan Ikan Untuk Meningkatkan Ekonomi Nelayan Desa Sendang Sikucing - Zaenal Arofi, Muhammad Labib; Kartikadarma, Etika; Najma Fatimah, Nandhita; Alvin Jaya Hulu, Alvin; Safa Firdaus, Muhammad Argya (Journal Of Human And Education (JAHE), 2024)
Fish are a valuable source of protein and healthy fats and contain essential nutrients for the body. In addition to direct cooking, fish can be processed into various products such as fish floss, fish balls, dumplings, and many other variations. In TPI Desa Sendang Sikucing, fish is primarily processed into salted fish and fish crackers by local residents. There has been a lack of innovative fish processing methods that could enhance the economic situation of the community and fishermen. To address this, a training program and cooking demonstration are necessary to improve the residents' skills in developing new fish products that can compete in the market and expand market demand. During the program, fish floss and fish sticks were among the products made. The enthusiasm of the participants was high; the women present were very eager to volunteer in the cooking process, which also motivated the male participants, creating a lively atmosphere. The participants gained new insights and experiences from the recipes and cooking demonstrations, which can help enhance the marketability of the fish products produced.